Switching clinic‐based cervical cancer screening programs to human papillomavirus self‐sampling: A cost‐effectiveness analysis of vaccinated and unvaccinated Norwegian women. Issue 3 (6th November 2021) - Pedersen, Kine; Portnoy, Allison; Sy, Stephen; Hansen, Bo T.; Tropé, Ameli; Kim, Jane J.; Burger, Emily A.
Abstract: Several countries have implemented primary human papillomavirus (HPV) testing for cervical cancer screening. HPV testing enables home‐based, self‐collected sampling (self‐sampling), which provides similar diagnostic accuracy as clinician‐collected samples. We evaluated the impact and cost‐effectiveness of switching an entire organized screening program to primary HPV self‐sampling among cohorts of HPV vaccinated and unvaccinated Norwegian women. We conducted a model‐based analysis to project long‐term health and economic outcomes for birth cohorts with different HPV vaccine exposure, that is, preadolescent vaccination (2000‐ and 2008‐cohorts), multiage cohort vaccination (1991‐cohort) or no vaccination (1985‐cohort). We compared the cost‐effectiveness of switching current guidelines with clinician‐collected HPV testing to HPV self‐sampling for these cohorts and considered an additional 44 strategies involving either HPV self‐sampling or clinician‐collected HPV testing at different screening frequencies for the 2000‐ and 2008‐cohorts. Given Norwegian benchmarks for cost‐effectiveness, we considered a strategy with an additional cost per quality‐adjusted life‐year below $55 000 as cost‐effective. HPV self‐sampling strategies considerably reduced screening costs (ie, by 24%‐40% across cohorts and alternative strategies) and were more cost‐effective than clinician‐collected HPV testing. For cohorts offered preadolescent vaccination, cost‐effective strategies involved HPV self‐sampling three times (2000‐cohort) and twice (2008‐cohort) per lifetime. In conclusion, we found that switching from clinician‐collected to self‐collected HPV testing in cervical screening may be cost‐effective among both highly vaccinated and unvaccinated cohorts of Norwegian women. Abstract : What's new? Human papillomavirus (HPV)‐based testing offers unique opportunities to improve cervical cancer screening. Among these opportunities is self‐sampling, in which samples can be collected at home and sent for laboratory analysis. Here, health and cost outcomes of program‐wide use of alternative HPV self‐sampling strategies were evaluated among birth cohorts of Norwegian women of varying HPV vaccination exposure. Among highly vaccinated and unvaccinated cohorts, self‐sampling was associated with lower screening costs and considered cost‐effective compared with clinician‐collected testing. The findings suggest that broader application of HPV self‐sampling can reduce costs with similar health benefits, though further studies are needed to assess the diagnostic accuracy of of population‐based self‐sampling and compliance behaviors among women offered self‐sampling.